Democratic Republic of Sao Tome and Principe : Staff Report for 2022 Article IV Consultation; Fourth Review Under the Extended Credit Facility Arrangement, Request for Waivers for Nonobservance of Performance Criteria, Modification of Performance Criteria and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2022)
Sao Tome and Principe has maintained macroeconomic stability, despite many challenges. The COVID-19 pandemic exacerbated long-standing socio-economic vulnerabilities, which were further compounded by persistent energy shortages and damages from the floods in end-2021. Growth declined in 2021 with power outages, while a targeted expansion of the cash transfer and food support programs provided needed relief to the most vulnerable. Strong grant financing remains critical for mitigating the impact of the pandemic. Vaccinations are proceeding, although the new COVID-19 variants pose risks for protracting the impact of the pandemic and require renewed actions to mitigate those risks. Parliamentary elections are expected in October 2022.